Muscle Coordination and Locomotion in Humans - Sylos-Labini, Francesca; Zago, Myrka; A Guertin, Pierre; Lacquaniti, Francesco; P. Ivanenko, Yury (Current Pharmaceutical Design, 2017)
Locomotion is a semi-automatic daily task. Several studies show that muscle activity is fairly stereotyped during normal walking. Nevertheless, each human leg contains over 50 muscles and locomotion requires flexibility in order to adapt to different conditions as, for instance, different speeds, gaits, turning, obstacle avoidance, altered gravity levels, etc. Therefore, locomotor control has to deal with a certain level of flexibility and non-linearity. In this review, we describe and discuss different findings dealing with both simplicity and variability of the muscular control, as well as with its maturation during development. Despite complexity and redundancy, muscle activity patterns and spatiotemporal maps of spinal motoneuron output during human locomotion show both stereotypical features as well as functional re-organization. Flexibility and different solutions to adjust motor patterns should be considered when considering new rehabilitation strategies to treat disorders involving deficits in gait.
Keywords: human locomotion